(untitled) (African Journal of Biomedical Research, 2019)
Tuberculosis is an infectious disease whose global burden is fueled by HIV and several socio-economic factors, with worse outcomes in low and middle-income countries. This retrospective study was carried out to ascertain the prevalence of TB and HIV among TB suspected patients in a tuberculosis clinic in Benin, Nigeria between 2nd January, 2015 and 31st December, 2017. Clinical records of patients who had registered under the DOTS program, University of Benin Teaching Hospital, Benin City during the study period were deployed. This included information on demographic data, medical history, laboratory results and treatment access. Statistical analysis was carried out on available data. A total of 667 patients were enrolled during the study period. The highest TB prevalence was observed in 2015 (44.3%) while the lowest was in 2017 (32.1%). There was no significant difference in the prevalence of TB in relation to gender (p = 0.2760). The age group 21-30 yrs showed the highest TB prevalence (47.9%) while the least prevalence was observed for the age group ≤ 10 yrs (11.1%); this finding was statistically significant (p < 0.0001). There was no statistically significant relationship between year of TB infection and HIV sero-status (p >0.05), although 8.4% of patients had HIV/TB co-infection. The prevalence of TB during this 3-year study review was 38.4%. Although a significant yearly decline in prevalence of TB was observed, the study draws attention on the need to address other socio-economic factors that play key roles in fueling the disease in Nigeria.